2020
DOI: 10.1111/den.13614
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal placement of a fully covered metal stent with a long string for distal malignant biliary obstruction without endoscopic sphincterotomy: Prospective multi‐center feasibility study

Abstract: Background Stent migration and sludge clogging are characteristic problems in biliary covered self‐expandable metal stent (SEMS) placement. Intraductal placement without endoscopic sphincterotomy (ES) may help reduce their occurrence. We examined the feasibility of intraductal placement of a covered SEMS with a long string without ES in patients with unresectable distal malignant biliary obstruction (MBO). Methods This was a prospective multi‐center observational study. Forty patients with distal MBO were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…For this purpose, biliary stenting above the papilla, namely, intraductal stenting, has been developed. [20][21][22] For successful intraductal stenting, biliary obstruction must be apart from the papilla of Vater. The efficacy of intraductal stenting has been reported particularly for hilar MBO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, biliary stenting above the papilla, namely, intraductal stenting, has been developed. [20][21][22] For successful intraductal stenting, biliary obstruction must be apart from the papilla of Vater. The efficacy of intraductal stenting has been reported particularly for hilar MBO.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of duodenobiliary reflux is a major concern in the management of biliary stenting. For this purpose, biliary stenting above the papilla, namely, intraductal stenting, has been developed 20–22 . For successful intraductal stenting, biliary obstruction must be apart from the papilla of Vater.…”
Section: Discussionmentioning
confidence: 99%
“…2). 20,34–37 Several series suggest that intraductal biliary stent placement without sphincterotomy may reduce the risk of stent dysfunction due to the duodenobiliary reflux and thereby, secure long patency 38,39 . However, in the setting of distal MBO, the distal stent end should often be positioned in the duodenal lumen to fully cover the stricture.…”
Section: Impact Of the Duodenobiliary Reflux On Biliary Stentsmentioning
confidence: 99%
“…20,[34][35][36][37] Several series suggest that intraductal biliary stent placement without sphincterotomy may reduce the risk of stent dysfunction due to the duodenobiliary reflux and thereby, secure long patency. 38,39 However, in the setting of distal MBO, the distal stent end should often be positioned in the duodenal lumen to fully cover the stricture. Therefore, investigations of antireflux mechanisms for biliary SEMSs may have substantial impact on quality of life among patients with nonresectable distal MBO.…”
Section: Impact Of the Duodenobiliary Reflux On Biliary Stentsmentioning
confidence: 99%
“…Despite multiple efforts to prolong stent patency and improve the safety, there is still no ideal CSEMS designed with perfect anti‐migration and anti‐duodenobiliary reflux properties, and with reduced risk for pancreatic duct obstruction. In this issue of DEN, Inoue et al , 9 reported a trial in which they placed a CSEMS above the papilla without endoscopic sphincterotomy (ES), with the hypothesis that an intact papilla would prevent migration and duodenobiliary reflux and that an intraductal stent would not block the pancreatic orifice. ES before SEMS placement may reduce obstruction of the pancreatic duct; however, ES was ineffective to prevent pancreatitis in UMDBO from pancreatic cancer, because the main pancreatic duct is obstructed and the pancreatic parenchyma is atrophied in many pancreatic cancer patients.…”
mentioning
confidence: 99%